Large Magnetic Gap in a Designer Ferromagnet–Topological Insulator–Ferromagnet Heterostructure. Issue 21 (31st March 2022) - Li, Qile; Trang, Chi Xuan; Wu, Weikang; Hwang, Jinwoong; Cortie, David; Medhekar, Nikhil; Mo, Sung‐Kwan; Yang, Shengyuan A.; Edmonds, Mark T.
Abstract: Combining magnetism and nontrivial band topology gives rise to quantum anomalous Hall (QAH) insulators and exotic quantum phases such as the QAH effect where current flows without dissipation along quantized edge states. Inducing magnetic order in topological insulators via proximity to a magnetic material offers a promising pathway toward achieving the QAH effect at a high temperature for lossless transport applications. One promising architecture involves a sandwich structure comprising two single‐septuple layers (1SL) of MnBi2 Te4 (a 2D ferromagnetic insulator) with ultrathin few quintuple layer (QL) Bi2 Te3 in the middle, and it is predicted to yield a robust QAH insulator phase with a large bandgap greater than 50 meV. Here, the growth of a 1SL MnBi2 Te4 /4QL Bi2 Te3 /1SL MnBi2 Te4 heterostructure via molecular beam epitaxy is demonstrated and the electronic structure probed using angle‐resolved photoelectron spectroscopy. Strong hexagonally warped massive Dirac fermions and a bandgap of 75 ± 15 meV are observed. The magnetic origin of the gap is confirmed by the observation of the exchange‐Rashba effect, as well as the vanishing bandgap above the Curie temperature, in agreement with density functional theory calculations. These findings provide insights into magnetic proximity effects in topological insulators and reveal a promising platform for realizing the QAH effect at elevated temperatures. Abstract : A ferromagnet/topological insulator heterostructure is fabricated comprising a sandwich structure of 2D ferromagnetic insulators with an ultrathin topological insulator in the middle. The ferromagnets induce magnetic order in the topological insulator via magnetic proximity leading to a quantum anomalous Hall insulator and large 75 meV magnetic bandgap. These findings reveal a promising platform for lossless transport applications at elevated temperatures.